Conspiracy Mentality, Self‑Efficacy, Self‑Control, Legal Cynicism, and Violent Extremist Intentions in Romanian Population - a Replicate Study (Studia Doctoralia Psychology and Educational Science, 2025)
We replicate Rottweiler and Gill’s model linking conspiracy beliefs to violent-extremist intentions (VEI) in a Romanian adult sample. Participants (N = 677) completed short measures of conspiracy beliefs, general self-efficacy, low selfcontrol (higher scores = lower control), legal cynicism, and VEI. We estimated four OLS models with HC3 robust standard errors, controlling for age (standardized midpoint, z) and gender. The results showed that conspiracy beliefs exhibited a small positive association with VEI in the baseline model (β ≈ .18, p < .001; R² ≈ .04) that attenuated to ~0 when either low self-control (β ≈ .46, p < .001; R² ≈ .22) or legal cynicism (β ≈.54, p < .001; R² ≈ .29) entered the model. Interactions (Conspiracy × Self-efficacy, × Self-control, × Legal cynicism) were small and non-significant; simple-slopes probes at −1 SD/mean/+1 SD yielded near-parallel lines. Findings replicate the modest conspiracy–VEI association while highlighting selfregulatory deficits and eroded legal normativity as dominant, additive correlates of extremist intentions in this context. Implications favor complementing counter-conspiracy messaging with interventions that strengthen self-regulation and enhance procedural justice and perceived legal legitimacy. Limitations include non-probability sampling, cross-sectional design, and reliance on self-report.
Keywords: conspiracy beliefs; violent-extremist intentions; legal cynicism; self-control; self-efficacy; Romania